Original paperImproved dosimetry in prostate brachytherapy using high resolution contrast enhanced magnetic resonance imaging: a feasibility study - Buch, Karen; Morancy, Tye; Kaplan, Irving; Qureshi, Muhammad M.; Hirsch, Ariel E.; Rofksy, Neil M.; Holupka, Edward; Oismueller, Renee; Hawliczek, Robert; Helbich, Thomas H.; Bloch, Nicolas (Journal of Contemporary Brachytherapy, 2014)
Purpose: To assess detailed dosimetry data for prostate and clinical relevant intra- and peri-prostatic structures including neurovascular bundles (NVB), urethra, and penile bulb (PB) from postbrachytherapy computed tomography (CT) versus high resolution contrast enhanced magnetic resonance imaging (HR-CEMRI). Material and methods : Eleven postbrachytherapy prostate cancer patients underwent HR-CEMRI and CT imaging. Computed tomography and HR-CEMRI images were randomized and 2 independent expert readers created contours of prostate, intra- and peri-prostatic structures on each CT and HR-CEMRI scan for all 11 patients. Dosimetry data including V 100 , D 90 , and D100 was calculated from these contours. Results: Mean V 100 values from CT and HR-CEMRI contours were as follows: prostate (98.5% and 96.2%, p = 0.003), urethra (81.0% and 88.7%, p = 0.027), anterior rectal wall (ARW) (8.9% and 2.8%, p < 0.001), left NVB (77.9% and 51.5%, p = 0.002), right NVB (69.2% and 43.1%, p = 0.001), and PB (0.09% and 11.4%, p = 0.005). Mean D 90 (Gy) derived from CT and HR-CEMRI contours were: prostate (167.6 and 150.3, p = 0.012), urethra (81.6 and 109.4, p = 0.041), ARW (2.5 and 0.11, p = 0.003), left NVB (98.2 and 58.6, p = 0.001), right NVB (87.5 and 55.5, p = 0.001), and PB (11.2 and 12.4, p = 0.554). Conclusions : Findings of this study suggest that HR-CEMRI facilitates accurate and meaningful dosimetric assessment of prostate and clinically relevant structures, which is not possible with CT. Significant differences were seen between CT and HR-CEMRI, with volume overestimation of CT derived contours compared to HR-CEMRI.